Anti-Mimicry of the Female Characters in Conrad’s Almayer’s Folly - Mugijatna Mugijatna Mugijatna; Sri Kusumo Habsari; Karunia Purna Kusciati (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
This research focuses on Joseph Conrad’s Almayer’s Folly  to explain the circumstance which leads to the rejection of Mrs. Almayer and Nina Almayer to embrace the dominant race and the reason why these characters choose to remain within ‘Othered’ identity. This study employs Ricoeur’s hermeneutics that applies two steps of reading: distantiation to obtain an objective understanding of the novel and an appropriation through putting the objective understanding of the novel in the socio-cultural context. This study attempts to offer the term “anti-mimicry”, borrowing Bhabha’s term’ to explain the subjectivity of the female character who stand out against the white domination to resist through savage and barbarous manners to mock the dominator, the white. Through the refusal to mimic, Conrad provides a space for Malay women consciousness to develop her subjectivity that could be construed as Conrad’s ambiguous perspective to white superiority in the colonialized era.